InDesign CS4 bible - Gruman, Galen (New Delhi : Wiley India Pvt. Ltd, 2009)
A guide to the page layout program explains how to navigate the interface, create documents, and work with text, color, graphics, and preflighting.
Includes index.
Keywords: Adobe InDesign (Electronic resource); Adobe InDesign (Electronic resource); Desktop publishing; Desktop publishing